2020
DOI: 10.5194/hess-24-2711-2020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of generalized non-data-driven lake and reservoir routing models for global-scale hydrologic forecasting of reservoir outflow at diurnal time steps

Abstract: Abstract. Large-scale hydrologic forecasts should account for attenuation through lakes and reservoirs when flow regulation is present. Globally generalized methods for approximating outflow are required but must contend with operational complexity and a dearth of information on dam characteristics at global spatial scales. There is currently no consensus on the best approach for approximating reservoir release rates in large spatial scale hydrologic forecasting, particularly at diurnal time steps. This resear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
(104 reference statements)
2
29
0
Order By: Relevance
“…Gutenson et al. (2020) compared observed inflow and outflow at several of the large reservoirs in the Missouri region. The study found that observed inflow at these reservoirs correlates well with observed outflow.…”
Section: Resultsmentioning
confidence: 99%
“…Gutenson et al. (2020) compared observed inflow and outflow at several of the large reservoirs in the Missouri region. The study found that observed inflow at these reservoirs correlates well with observed outflow.…”
Section: Resultsmentioning
confidence: 99%
“…These reservoir operation schemes can be applied to ungauged basins and compared with the satellite-based method. Little research has been conducted to address how well these reservoir operation schemes perform and whether a particular reservoir operation scheme is suited for a specific type of reservoirs (Gutenson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dam operation is a challenge, especially due to the complexities and the non-linearity of the operations which may be driven by anthropogenic and environmental influences (Gutenson et al, 2020). For instance, a drought following the 2018 Kerala flood in India was worsened because dams had been emptied in preparation for floods, but the dam's water release combined with intense precipitation downstream aggravated downstream the flood and its impacts (Lal et al, 2020).…”
mentioning
confidence: 99%
“…et al, 2018;Veldkamp et al, 2017), and assessment of biotic disturbances (Latrubesse et al, 2017;Maavara et al, 2020;Sabo et al, 2017). The consideration of dams on hydrological models improves the model performance downstream (Gutenson et al, 2020), but the lack of information on dams may jeopardize its modelling applications, specially at a national level (Zhao et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation